Predictive Role of Ultrasound Remission for Progressive Ultrasonography-Detected Structural Damage in Patients with Rheumatoid Arthritis. (February 2022) - Liu, Feifei; Li, Wenxue; Zhu, Jiaan; Liu, Fang; Fan, Wenting; Chen, Zheng
Regarding the persistence of subclinical synovitis, the concept of ultrasound remission has been proposed in addition to clinical remission. However, there have been no studies that explored the different time points of ultrasound remission to predict non-progressive structural damage. Given this, the aim of our study is to explore whether early ultrasound remission in patients with rheumatoid arthritis (RA) has predictive value for non-progressive structural damage in the subsequent 12 months. Sixty-one patients with RA were prospectively studied. Synovial hypertrophy, power Doppler (PD) signal, and bone erosions of bilateral wrists, metacarpophalangeal joints I–V, and proximal interphalangeal joints II–III were assessed by ultrasonography at baseline and at 3, 6, and 12 months. Ultrasound remission was defined as no PD signal. Clinical remission was defined as Disease Activity Score in 28 Joints <2.6. Ultrasonography-detected joint damage progression was defined as increase in bone erosion score of ≥1 in the subsequent 12 months. Baseline ultrasonographic factors were not significantly correlated with progressive ultrasonography-detected joint damage in patients with RA at 12 months (all p>0.05). Ultrasound remission at 3 and 6 months was significantly correlated with non-progressive ultrasonography-detected structural damage at 12 months (p=0.006 and p=0.004), with relatively low sensitivity and high specificity. Clinical remission at 3 months was significantly correlated with non-progression of ultrasonography-detected structural damage at 12 months (p=0.029), with relatively low sensitivity and moderate specificity. Ultrasound remission at 3 and 6 months has high specificity in predicting non-progressive structural damage in patients with RA at 12 months; however, the sensitivity is limited.